Bigger, faster, stronger : the proven system for developing athletes - Shepard, Greg, ....-; Goss, Kim, ....- (Champaign : Human Kinetics, 2017)
Bigger Faster Stronger (BFS) is the premier performance program for high school and college sports. BFS and the book Bigger Faster Stronger have led teams to more than 500 state championships, and that was just the warm up. Now in its third edition, Bigger Faster Stronger is ready for the next generation of athletes and the next level of performance. Inside, you'll find training guidelines for in-season and off-season weight training, as well as the latest strategies for breaking through plateaus, developing peak strength, and increasing power, flexibility, speed, and agility. You'll learn the proper exercise techniques for the big four lifts, as well as multiple variations and safety protocols. You'll also find recommendations for integrating new equipment, athlete monitoring systems, and other technology into your program to ensure maximum effectiveness and performance gains. Bigger Faster Stronger can accommodate any sport and every level of competition. Safe, effective, and relied on by thousands of athletes, coaches, and administrators, it is the proven performance program you can trust.
Keywords: Krachttraining